THE INFLUENCE OF DIVERSITY ORIENTED LEADERSHIP TOWARDS KNOWLEDGE SHARING THROUGH TRANSPARENT INTERNAL COMMUNICATION, INTRINSIC NEEDS SATISFACTION, AND JOB ENGAGEMENT - Ellyana Angawati; Kurniawati Kurniawati (Jurnal Ekonomi Trisakti, 2022)
There are many ways for companies to retain employees. The approach simply proposed that companies would benefit from employees that are loyal in order to create knowledge sharing throughout the company, which are important and necessary in achieving the goal and mission of the company. Communication styles, leadership methods, including the employees’ necessity as one of the parameters for the employees to continue to share their knowledge within the company. This research aims to maximize the company and the employee mutualistic relationships which requires both understanding. Exploration and approach between company with employees in many aspects such as managerial level, openness, boundness, and the employee’s demand are also measured and comprised. The literature review argue that these are the ways to improve trust, experience, satisfaction and commitment, so that there are tight relationships with each other especially in crises situation. This research uses purposive sampling with age ranging from 23 years old until 70 years old with associate degree to doctoral degree in many types of industry, variant income, managerial level, and duration of work at the company. This research is suitable for someone who is a decision maker in the company to improve the company. The data uses SPSS 25 and AMOS 21 methods for analyzing. Majority of the variables shows that the variables are positive related. Therefore, this research could use for companies’ improvement towards employee’s retentions. In addition, acknowledgement from employees would lead to employee’s knowledge sharing.